Uji Efektivitas Ekstrak Daun Sirih Hijau (Piper betle L.) untuk Menghambat Pertumbuhan Jamur Geotrichum sp. Penyebab Penyakit Busuk Asam pada Jeruk Lemon - Pramuditha, Ratih; Suprapta, Dewa Ngurah; Sudarma, I Made (Agrotrop : Journal on Agriculture Science; Vol 14 No 3 (2024), 2024)
Effectiveness of Green betel ( Piper betle L.) Leaf Extract to I nhibit the Growth of the Fungus Geotrichum sp. , the Cause of Sour Rot Disease in Lemon . Sour rot disease, caused by the fungus Geotrichum sp., is an important post-harvest disease of citrus fruits in most parts of Indonesia and the world. Therefore, it is necessary to develop environmentally friendly disease control methods, one of which is by using botanical pesticides. Green betel leaf is one of the plants whose extract is used as a botanical fungicide. This study aims to test the effectiveness of green betel leaf extract against the fungus Geotrichum sp., which causes sour rot disease in lemon. The colony test uses eight extract concentrations, namely 0,8%, 0,16%, 0,32%, 0,40%, 0,48%, 0,56%, 0,64%, and control. The in vivo test uses five concentrations, namely 0,5%, 0,75%, 1%, 1,25%, 1,5%, and control. The research results showed that the minimum concentration of green betel leaf extract that suppressed the colony growth of the fungus Geotrichum sp. is 0.40% which means it is suitable for use as a botanical fungicide. On in vivo test, green betel leaf extract inhibits fungal growth and infection and can suppress the growth of Geotrichum sp. An extract concentration of 1,5% can suppress the damage of lemons by Geotrichum sp., amounting to 47.16%.